(untitled) (Journal of Academic Research, 2025)
Background Proximal humeral fractures (PHFs) are the third most common fracture in older patients. The purpose of the study was to prospectively evaluate the outcomes of PHF fixation with a locking blade nail (LBN) or locking plate (PHILOS) osteosynthesis in a homogeneous elderly patient population. Methods Inclusion criteria were an age > 60 years and the capacity to give informed consent. Patients with isolated tuberosity fractures, previous trauma or surgery, advanced osteoarthritis, fracture dislocation, pathological fractures, open fractures, neurological disorders, full-thickness rotator cuff tears, fracture line at the nail entry point or severely reduced bone quality intra-operatively were excluded. Eighty-one patients with PHFs were randomized to treatment using LBN or PHILOS. Outcome measures comprised Constant score, age and gender adjusted Constant score, DASH score, VAS for pain, subjective overall condition of the shoulder (1–6) and active shoulder range-of-motion in flexion and abduction. Plain radiographs were obtained in two planes. All data were collected by an independent observer at 3, 6 and 12 months postoperatively. Results Thirteen patients were excluded intra-operatively due to rotator cuff tears, fracture morphology or poor bone-quality. Of the remaining 68 patients, 27 in the LBN and 28 in the PHILOS group completed the full follow-up.